Are people's economic wants insatiable? Examining the psychology of a basic economic belief. - Paul G. Bain; Renata Bongiorno (ZBW – Leibniz Information Centre for Economics, 2024)
Despite widespread claims by economists that humans have unlimited economic wants, evidence for this psychological claim is sparse. Here we focus on a common interpretation of unlimited wants as insatiable – unfulfilled wants persist even at higher incomes because new wants always emerge to replace satisfied wants. We analyzed a representative 16-year multi-wave US dataset (N=11865) previously used to show that economic wants are insatiable based on highly selective subsets of these data. Using the full dataset shows that having insatiable wants is far from universal – about a third reported no unfulfilled economic wants, and on average people with higher incomes had fewer wants. Additional analyses showed that many people did not aspire to wealth in their conception of “the good life”, and the extent of unfulfilled wants varied over time. This assumption about universal human nature is not supported, calling into question the theories and policies it informs.
Keywords: A10; A12; A13; 330; unlimited wants; insatiability